It's the Great Pumpkin, Charlie Brown [videorecording (DVD)] - Mendelson, Lee; Melendez, Bill; Schulz, Charles M. (Charles Monroe), 1922-2000 (Distributed by Warner Home Video, 2008)
Longtime believer, Linus believes that this year the Great Pumpkin will come and he decides to keep watch all night in the pumpkin patch to welcome him. Charlie Brown dresses up as a ghost, but does not scare up the usual kinds of Halloween loot when trick-or-treating. Snoopy crashes into Violet's party, as well as Linus' vigil.